IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SQ3R TECHNIQUE - Musrifah, Musrifah; Yuliana, Yohanes Gatot Sutapa; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis Classroom Action Research was aimed to improve students’ reading comprehension of biographical recount text through Survey, Question, Read, Recite, and Review (SQ3R) technique. The tenth grade students of SMKN 3 Pontianak were the subject of this research. The findings showed that the students’ problems in understanding biographical recount text especially in finding main idea and detail information were solved by using SQ3R as their reading technique. The students also responded to the implementation of SQ3R technique positively. They become active learners in generating questions, providing and presenting the answers and discussing their work together. Based on the findings, it is concluded that SQ3R technique can improve comprehension in reading biographical recount text by providing a structured stages for reading activities.  Key words: Reading Comprehension, Recount Text, SQ3R Technique